Information Seeking Behaviour of Senior High School Student on General Election in Indonesia - Rahman, Margareta Aulia (Universitas Airlangga, 2015)
The development of information technology affects students in searching and finding information, particularly information regarding the General Election. Theexplosion of information on mass media about the elections resulted impact (both positive and negative) to the potential voters. Nowadays, media plays role as a tool for political parties to lead public opinion to support their parties. Based on the data provided by General Election Commission (KPU) in 2014, 20% of voters were identified as students (teens). This is a qualitative research with case study methodwhich aims to gain insight about interpretation, understanding, perceptions and feelings of teenage votersâ behavior in searching and finding information about general election in Indonesia year 2014. The data were collected by conducting interview and observation. Informants (six persons) in this study were students, aged 17-18 years, who studying in government senior high school in Depok. The results of this study indicates that informants using social media to keep update about general election. Besides, they also gain information from their parents and close friends. Unfortunatelly, they were not able to identify which information which are correct or not, so they rely on people around them to make sure whether they did right decision. Therefore, this study also suggest that KPU needs to develop promotion strategy that suitable for teens about general election.